G protein signaling mechanisms in the retina - Sampath, Alapakkam P.; Martemyanov, Kirill A. (Springer Series in Vision Research, 2014)
We have learned a great deal about the organization and function of GPCR pathways, and the role that they play in vision. The information gained from these studies has provided, and will continue to provide, critical insights to further our understanding of complex GPCR pathways in the central nervous and endocrine systems. In essence, the retina is the first 'optogenetically'-driven circuit with clearly understood physiology. Thus, studying GPCR-driven pathways in the retina will likely guide the interpretation of optogenetic experiments, which are increasingly utilized to study central circuits. Collectively, these signaling pathways allow the retina to represent visual space over a wide range of light intensities and to synchronize its function to the day/night cycle. G protein Signaling Mechanisms in the Retina summarizes our current understanding of the organizational principles of GPCR pathways, using insights derived from the study of the retina. The book highlights several G protein signaling cascades, including phototransduction, ON bipolar cell signaling, dopaminergic pathways, and ipRGC signaling.